Evaluation of the relationship between serum and humor aqueous raftlin (Rftn1) levels and diabetic retinopathy - Mesen Selma; Comez Aysegul; Mesen Ali; Beyoglu Abdullah; Seyithanoglu Muhammed (Türk Biyokimya Dergisi)
Comparing serum and humor aqueous (HA) raftlin levels in diabetic patients and control group.